Óleos essenciais como antiparasitários contra Gyrodactylus lilianae e Ichthyophthirius multifiliis - Murari, Anelise Levay (2016)
Gyrodactylosis and ichthyophthiriasis resulted in significant economic losses in fish farming. Several products have been used in the treatment of these diseases and few showed satisfactory antiparasitic efficacy. Thus, this work aimed to obtainew antiparasitic drugs from essential oils (EOs) of native medicinal plants: Aloysina gratissima (AEO), Nectandra megapotamica (MEO) e Nectandra grandiflora (GEO). Tchhreo meastsoegnratipahl y ocilosu pwleedr et o ombatasisn esdp ecbtyro mheydtrryo dainsdti lltaot ioflna maen ido niaznaatiolynz edde tebcyt org. aIns vitro assays against Gyrodactylus lilianae were conducted and the concentrations tested were 9 to 90 mg L-1 (AEO) 50 to 500 mg L-1 (MEO) and 10 to 100 mg L-1 (FGroEmO )t,h aei minin vgi ttroo dreetseurlmtsi,n ein thveiv oe ffterecatitvme ecnotn pcreonttorcaotiolsn f(oEr Cg)y orovdear ctthyelo esxisp ohsauvree btimeeen. proposed for each EO, using immersion baths. Juvenile silver catfish (R. quelen) were subjected to two baths with a 24 hour interval between them, at concentrations oafn t9ip0a mrags iLti-c1 faocrt i2v ihty (AagEaOin),s t2 0th0e m togm Lo-1n (tMs EoOf I)c ahnthdy o5p0h mthgir iLu-s1 (mGuElOtif)il,i ibs owtha sfo er v1a hlu. aTtheed in vitro for AEO (9 to 750 mg L -1), while for MEO and GEO the concentrations tested were equivalent to those used against G. lilianae. The treatment protocol against is ichthyophthiriasis consisted of bath lasting five days at a constant concentration of AEO (9 and 15 mg L-1), while for GEO the concentration tested was 15 mg L-1. The main constituents of the AEO were: germacrene D (19.98%), β-caryophyllene (12.97%) and p-cymene (11.88%). However, for MEO α-pinene (25.5%), β-pinene (15.4%) and globulol (10.5%) were the major components, while GEO presented dtheeh ymdaroinf uckoinmopnoen e(1n7ts.0. 8A%ll )t,e sbtiecdyc EloOgse rsmhaocwreedn ea n(1ti1p.a4r7a s%itic) aanctdiv iαty-p aingeanines t( 4G.9. 8li%lia)n aaes and I. multifiliis in in vitro assays. The protocols applied to gyrodactylosis showed efficacy of 98.4% (AEO), 90.7% (MEO) and 95.6% (GEO) after the first bath, while tthhere ea nEthOeslm teinsttiecd e ifnfe vcitvivoe naegsasin swta Gs . 1l0ili0a%na efo, ro anllly EGOEsO a fctaeur stehde mseocrotanldity b oaft hju. vOefn itlhees (8.33% after the second bath). AEO was not effective for treating ichthyophthiriasis, however GEO was able to increase the survival of treated fish. AEO and MEO have potential for development of new commercial antiparasitic drugs for the treatment of gyrodactylosis, while GEO have potential use for the control of ichthyophthiriasis.